A longitudinal study of personality-occupation congruence on career - Schellenberg, Claudia; Krauss, Annette; Hättich, Achim (Swiss Journal of Educational Research, 2017)
There is amazingly few research into personality-occupation congruence in a longitudinal study. Drawing on Holland, our study investigates congruence over 36 years in a representative sample of the German-speaking part of Switzerland (N=805). Two different representations of congruence are examined: Profile-correlations based on raw scores and comparison of the first three letters of the RIASEC (Zener-Schnuelle Index). Personality was measured with the Adjective Check List and occupational interests. Results indicated that there is a significant correlation between personality and occupation over the 36 years. This is associated with life satisfaction and satisfaction in different domains.